Power and hunger : the state, farmers, and the Grain Marketing Board in Zimbabwe, c. 1980-2017 - Mashingauta, Aisha Hatina (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.